An Analysis of Code Mixing Used in Novel “Koala Kumal” by Raditya Dika - Desva Ariasanti; Sastika Seli; Dewi Syafitri (EDULIA: English Education, Linguistic and Art Journal, 2022)
ABSTRACT The problem of the study was “What are the types, meanings, and functions used in novel ‘Koala Kumal’ by Raditya Dika?” The objectives of the study were to find out the types, meanings, and functions of code mixing used in novel “Koala Kumal” by Raditya Dika. This study mainly aimed to describe code mixing found in novel “Koala Kumal”. The writer used a qualitative descriptive method to classify and analyze the data. The data were analyzed through some steps including identification, classification, reduction, description, and conclusion. After the data were analyzed, the writer found the types, the meanings, and the functions of code mixing in novel “Koala Kumal”. The types of code mixing that were found in novel “Koala Kumal” were insertion of word (112 words) and phrase (53 phrases), alternation (4 clauses), and congruent lexicalization (3 words). Denotative meanings (170 words and phrases) and connotative meanings (65 words, phrases, and clauses) were found in novel “Koala Kumal”. The functions of code mixing which found were to involve the topic of conversation (146 words and phrases), adapt with new participant (21 words, phrases, and clauses), and express solidarity (5 words). In summary, code mixing which is used by Raditya Dika in his novel had the purpose to inform and convey the topic which Raditya talk about, then to express his feeling, and also to measure the level of solidarity among the relationship between Raditya Dika with other people in intimate and distance relationship. Key word: code mixing, novel